2017
DOI: 10.3389/fpls.2017.01417
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Diversity and Short-term Response to Shading Stress in a Threatened Seagrass: Does Low Diversity Mean Low Resilience?

Abstract: Seagrasses that are predominantly clonal often have low levels of genetic variation within populations and predicting their response to changing conditions requires an understanding of whether genetic variation confers increased resistance to environmental stressors. A higher level of genetic diversity is assumed to benefit threatened species due to the increased likelihood of those populations having genotypes that can persist under environmental change. To test this idea, we conducted an in situ shading expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 61 publications
(79 reference statements)
0
21
0
2
Order By: Relevance
“…This threatens population survival, as genetic diversity is an important determinant of long-term population persistence (Frankham 2005). Indeed, high genetic diversity bolsters the resilience of populations, because they harbour a higher adaptive capacity with which to respond to perturbations such as disease, environmental change, or declining environmental conditions (Hughes and Stachowicz 2004;Ehlers et al 2008;Evans et al 2017). Low genetic diversity is also related to inbreeding depression, where recessive deleterious alleles are more likely to combine within individuals and reduce fitness (Whitlock 2000;Reed and Frankham 2003;Charlesworth et al 2009), further compromising the long-term prospects for survival of the population.…”
Section: Introductionmentioning
confidence: 99%
“…This threatens population survival, as genetic diversity is an important determinant of long-term population persistence (Frankham 2005). Indeed, high genetic diversity bolsters the resilience of populations, because they harbour a higher adaptive capacity with which to respond to perturbations such as disease, environmental change, or declining environmental conditions (Hughes and Stachowicz 2004;Ehlers et al 2008;Evans et al 2017). Low genetic diversity is also related to inbreeding depression, where recessive deleterious alleles are more likely to combine within individuals and reduce fitness (Whitlock 2000;Reed and Frankham 2003;Charlesworth et al 2009), further compromising the long-term prospects for survival of the population.…”
Section: Introductionmentioning
confidence: 99%
“…), in conjunction with the demographic history and genetic variation at the meadow scale, can affect resistance within species. For example, the existence of a large and diverse number of genotypes within meadows provides an ideal scenario for adaptation to, and recovery from, environmental stress (Salo, Reusch, & Boström, ), including reduced light levels (Evans, Vergés, & Poore, ). Reductions in light availability are one the main perturbations affecting the physiology and overall fitness of seagrasses world‐wide (Leoni, Vela, Pasqualini, Pergent‐Martini, & Pergent, ); decreased shoot survivorship and altered vegetative development can consequently affect associated epifauna (Gartner, Lavery, McMahon, Brearley, & Barwick, ).…”
Section: Introductionmentioning
confidence: 99%
“…While seagrass meadows often consist of just one or a few species, it is thought that genotypic diversity plays an equivalent role to species diversity in other ecosystems ( Hughes and Stachowicz, 2011 ; Massa et al, 2013 ; Jahnke et al, 2015 ). Field and mesocosm studies have shown that higher levels of genotypic diversity are positively related to several ecological aspects, including: resistance ( Hughes and Stachowicz, 2004 ; Massa et al, 2013 ; Evans et al, 2017 ), recovery ( Hughes and Stachowicz, 2004 , 2011 ), productivity and faunal abundance ( Reusch et al, 2005 ), restoration success ( Reynolds et al, 2012 , 2013 ), mitigation of the effects of grazing ( Hughes et al, 2010 ), and the ability to cope with the effects of climate change ( Reusch et al, 2005 ; Ehlers et al, 2008 ). A meta-analysis of studies on Posidonia oceanica showed that genetic diversity (allelic diversity, genotypic richness, and observed heterozygosity) was weakly, but significantly, associated with the extents of several disturbance types, namely shipping, pollution, and cumulative impact ( Jahnke et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%